Sprout Test of Seven Types of Sumatran and Javan Rice with the Addition of Liquid Organic Fertilizer - Elis Nina Herliyana; Fifit Kultsum; Dewi Sukma; Deden Hidayatullah; Abdul Munif (Institut Pertanian Bogor, 2025)
Rice productivity in Indonesia has declined due to a decrease in land area between 2018 and 2019. Another issue with rice seed dormancy is a reduction in productivity. Liquid organic fertilizer (LOF) is one way to overcome seed dormancy. The purpose of this study is to investigate the effect of soaking rice seeds in LOF on germination (viability), normal vigor of growing seeds (vigor), and germination rate. This study took place in the greenhouse and laboratory of the Department of Silviculture, Faculty of Forestry and Environment, IPB, from September to October 2022. Immersion procedures, planting, and data analysis were all steps in monitoring rice germination studies on four types of West Sumatra rice, one variety of West Java rice, and two varieties of rice from the Sukamandi Rice Research Centre. Soaking rice seeds in LOF affects their germination capacity and rate. Pandan Wangi had the maximum germination capacity and average seed count on filter paper medium, while Inpara 8 had the highest germination capacity and average seed count on vermicompost media with a 1:3 immersion. Anak Daro and Cikawasen had the fastest germination rates on filter paper media, whereas Pandan Wangi did the best on vermicompost media. Keywords: Liquid organic fertilizer, local rice, seed dormancy